Kinetics of Palm Oil Transesterification Using Double Promoted Catalyst CaO/KI/Î³- Al2O3 - Nyoman Puspa Asri; Kusno Budikarjono; Suprapto Suprapto; Achmad Roesyadi (Journal of Engineering and Technological Sciences, 2015)
Double promoted catalyst (CaO/KI/Î³-Al2O3) was used as the catalyst for transesterification of palm oil into biodiesel. The experiment was carried out in a batch reactor consisting  of a three-neck glass flask (500 ml capacity) equipped with a reflux condenser, thermometer and magnetic stirrer. Kinetic study was  carried out with methanol under reflux conditions  at different temperatures (35-75°C) and different times of reaction (1-7 hours). The effects of temperature and time of the reaction on the conversion of palm oil into biodiesel and reaction rate constants were investigated. The results showed that the conversion and rate constants of reaction increased with the increasing of the reaction temperature. The highest conversion of 97% was obtained at 65°C and 5 hours  of reaction time. Meanwhile, the activation energy and the frequency factor were 15.47 kJ/mol and 1.22.102, respectively.